2018
DOI: 10.15366/reice2018.16.2.007
|View full text |Cite
|
Sign up to set email alerts
|

Hacia la Implantación de Comunidades Profesionales de Aprendizaje Mediante un Liderazgo Distribuido. Una Revisión Sistemática

Abstract: El presente artículo se corresponde con una revisión sistemática que analiza la relación del liderazgo, en su variante distribuida con las comunidades profesionales de aprendizaje, ambos conceptos muy demandados por las investigaciones internacionales. El proceso ha seguido patrones llevados a cabo en otras revisiones sistemáticas indexadas en revistas de gran impacto, para augurar la sistematicidad del mismo. Durante el mismo, se hizo una búsqueda minuciosa de artículos ubicados en la base de datos Scopus, du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
3
0
5
Order By: Relevance
“…In addition, there is a relationship, albeit weak, between the actions of the management to create an environment of collaboration in the educational organization and the distribution of responsibilities and joint decision-making in the center. These results coincide with other studies that have pointed to "empowering" as a means of school improvement (García-Martínez, Higueras-Rodríguez & Martínez-Valdivia, 2018;Harris, 2014). According to some authors, the direction as the formal leader of the center must empower teachers to assume pedagogical responsibilities, which motivate them to work towards a common project.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In addition, there is a relationship, albeit weak, between the actions of the management to create an environment of collaboration in the educational organization and the distribution of responsibilities and joint decision-making in the center. These results coincide with other studies that have pointed to "empowering" as a means of school improvement (García-Martínez, Higueras-Rodríguez & Martínez-Valdivia, 2018;Harris, 2014). According to some authors, the direction as the formal leader of the center must empower teachers to assume pedagogical responsibilities, which motivate them to work towards a common project.…”
Section: Discussionsupporting
confidence: 88%
“…On the other hand, organizational decentralization entails greater participation, shared decision-making, the strengthening of trust in the educational center and fluid and effective relationships among all educational agents. These factors represent an important advance in the initiation of internal change processes necessary for any school to achieve school improvement (García-Martínez, Higueras-Rodríguez & Martínez-Valdivia, 2018). In an investigation carried out by Shaked & Schechter (2017), it was found that the systemic thinking of intermediate leaders are characterized by four characteristics: "(1) seeing wholes; (2) using a multidimensional view; (3) influencing indirectly; and (4) assessing significance" (p. 699).…”
Section: García-martínez and Tadeumentioning
confidence: 99%
See 1 more Smart Citation
“…Se reconoce entonces la necesidad de establecer comunidades de aprendizaje profesional a través de un liderazgo distribuido, en tanto ello fomenta la organización, la colaboración y el empoderamiento docente. Así, la flexibilidad de las estructuras organizativas ofrece oportunidades para la mejora del capital profesional (Higueras-Rodríguez y Martínez-Valdivia, 2018). Puesto que un modelo de innovación mediado por TIC desde una comunidad profesional de aprendizaje permite el aprender en tiempo real y lograr niveles más altos de participación (Yang, 2019).…”
Section: Discusión Y Conclusionesunclassified
“…Networking has come to the forefront in recent years and has become a beacon of good practice for innovation and improved learning (Azorín, 2017;López-Yañez et al, 2014;Prenger et al, 2021;Robinson et al, 2020;Schnellert & Butler, 2020). The use of networks in school settings therefore offers many opportunities and promising prospects (Azorín, 2020a;García-Martínez et al, 2018;Murillo & Krichesky, 2015; Organisation for Economic, Co-operation and Development, 2019;Scheleicher, 2018). However, while the potential of learning networks has been recognized as an efficient strategy for improvement in schools, it has also been noted that there are too many teachers who work on their own, and too many isolated schools and researchers, which leads to the conclusion that only by working together can true change be implemented (Murillo, 2009).…”
Section: Introductionmentioning
confidence: 99%